INVESTIGATION OF STUDENTâS WORK ON FRACTIONâS IMPLEMENTATION BASED ON THE JOURNAL ENTITLED âA STUDY ON THE ABILITY OF SIXTH GRADE STUDENTS IN TIBETAN AREAS TO SOLVE MATH PROBLEMSâ - Pramasdyahsari, Agnita Siska (AKSIOMA, 2015)
This study aims to analyse the studentâs performance in solving fractions and explore the studentsâ understanding related with fraction. The subjects of this study are 2 students of grade 6 and 1 student of grade 7. In this case, as an observer who implement the mathematics problem based on the questions which is adapted from the journal, it just analyse about the studentsâ work related to the studentsâ understanding about fraction. No matter how the studentsâ ways and their methods to solve the problem which is provided, whether it is true or vice versa, because the question enable of open answer, the important thing is we will recognise the studentsâ understanding about fraction. Through analyse from their worksheet and interview, it can be said that there are several reasons why they did as they wrote in. Keywords: Fraction,Â  Understanding, SixthÂ  grade students.